Shared guard: principle of the best interests of children and adolescents as a guide for custody decisions (Research, Society and Development, 2021)
This work aims to study shared custody in light of the principle of the best interests of children and adolescents in light of legislation and jurisprudence. Through a study of family power and shared custody itself. The countless consequences of breaking the marriage bond, especially in the lives of children, are highlighted. With global evolution in recent decades, sexual revolution and questioning of religious fundamentalism, child custody has become a chronic problem in capitalist society. Thus, this work aims to study the relationship between shared custody and the principle of the best interests of children and adolescents, demonstrating its importance and effects in relation to children after the marital bond is broken. In view of the above, the need to observe the major changes that have taken place in society was evidenced, which were cultural, socioeconomic, political and about preferences in families and relationships between parents and children, highlighting a large increase in the rupture of marital ties . A qualitative bibliographic and documentary research was chosen, searching electronic databases, scientific articles and journals, the main one being the Scientific Electronic Library online (ScieLo). Finally, considering the principle of the best interests of children and adolescents, shared custody, by providing greater family coexistence, as well as an effective participation of both parents in the education of their offspring, are essential factors for the preservation of the infants' emotional well-being, reveals itself as a model that leads to the realization of the principle of the best interests of children and adolescents.